1998
DOI: 10.1161/01.hyp.31.1.435
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Exacerbates Hypertension and Reduces Pressure-Natriuresis in Male Spontaneously Hypertensive Rats

Abstract: Abstract-Studieswere performed m intact male and female, gonadectomlzed male and female, and gonadectomzed female rats gwen testosterone for 5 weeks to mve$tlgate the role played by testosterone m altered blood pressure control and pressure-natrmreas m male SHR Serum testosterone levels reached a peak at 12 weeks of age m Intact male SHR Systohc blood pressure, measured weekly from 5 to 20 weeks of age, was slmllar between groups until 12 weeks of age when blood pressure became higher m males (195+3 Key Words:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
257
1
23

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 291 publications
(302 citation statements)
references
References 17 publications
18
257
1
23
Order By: Relevance
“…6,7 This difference in blood pressure between intact and castrated males is still present at 8 months of age, the oldest age we have studied thus far. 8 We also found that the renin-angiotensin system (RAS) plays an important role in the development of hypertension in young SHR, because blockade of the RAS with converting-enzyme inhibitors removed the sex difference in blood pressure, and testosterone treatment of ovariectomized females was not capable of increasing their blood pressure.…”
mentioning
confidence: 88%
“…6,7 This difference in blood pressure between intact and castrated males is still present at 8 months of age, the oldest age we have studied thus far. 8 We also found that the renin-angiotensin system (RAS) plays an important role in the development of hypertension in young SHR, because blockade of the RAS with converting-enzyme inhibitors removed the sex difference in blood pressure, and testosterone treatment of ovariectomized females was not capable of increasing their blood pressure.…”
mentioning
confidence: 88%
“…9 As shown in Figure 1, in younger SHR (ages 4 and 8 months), females have lower blood pressure than males. 6,9,10 However, by age 16 to 18 months, the blood pressure has increased by 25 to 35 mm Hg, compared with young females, and 15 mm Hg when compared with 8-month-old females. In addition, the sex difference in blood pressure no longer exists because of the increase in blood pressure in old females, whereas blood pressure in male SHR remains fairly stable after age 8 months.…”
Section: Animal Model For the Study Of Postmenopausal Hypertensionmentioning
confidence: 99%
“…The prevalence of essential hypertension is higher in men than in age-matched premenopausal women. 1,2 In hypertensive rat models, such as spontaneously hypertensive rats (SHR) 3,4 and Dahl-salt hypertensive rats, 5,6 males have higher blood pressures than do females.…”
mentioning
confidence: 99%